Ultra-flexible TiO2/SiO2 nanofiber membranes with layered structure for thermal insulation - Zhenfeng Guo; Ze Zhu; Xiaoqian Zhang; Ying Peng; Ziting Huang; Xinqiang Wang; Luyi Zhu; Yongshuai Xie; Guanghui Zhang; Benxue Liu; Dong Xu (Journal of Materiomics)
High-performance thermally insulating ceramic materials with excellent mechanical and thermal insulation properties are essential for thermal management in extreme environments. In this work, SiO2 was introduced into the crystalline lattice and grain boundary of TiO2 to inhibit its phase transition and grain growth. Meanwhile, layered TiO2/SiO2 nanofiber membranes (TS NFMs) were designed and prepared. The TS NFMs had lightweight (44 mg/cm3), high tensile strength (4.55 MPa), ultra-flexibility, and low thermal conductivity (31.5 mW·m−1·K−1). The prepared TS-1100 NFMs had excellent buckling fatigue resistance, which could undergo 100 buckling-recovery cycles at up to 80% strain. Low density and high diffuse reflectance endow the TS NFMs with excellent thermal insulation effects. A single-layer nanofiber membrane was composed of multiple layers of nanofibers. According to the principle of multi-level reflection, the multilayer structure had a better near-infrared reflection effect. Through the stacking effect of layers, a 10 mm thick sample composed of about 300 layers of nanofiber membranes could reduce the hot surface temperature from 1,200 °C to about 220 °C, demonstrating an excellent comprehensive thermal insulation effect. The layered TS NFMs with ultra-flexibility, high tensile strength and high-temperature resistance (1,100 °C) provide a dominant pathway in producing materials in extremely high-temperature environments.